2010
DOI: 10.1159/000264617
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Guideline Conformity on Breast Cancer Therapy: Results of a 13-Year Retrospective Cohort Study

Abstract: Background: To date, few studies have investigated whether the implementation of national breast cancer guidelines fulfills the goal to optimize the national standard of care. Therefore, we aimed to evaluate retrospectively the guideline-related 13-year data on breast cancer patients treated at our institution. Patients and Methods: In a retrospective cohort study, the records of a total of 2,231 patients with primary breast cancer treated during the period of 1992–2005 at the Department of Obstetrics and Gyne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 9 publications
1
22
0
3
Order By: Relevance
“…One reason for this high concordance between treatment modalities in both departments is the high adherence to current national breast cancer treatment guidelines [19], ranging between 78.0 and 95.6% of all indications being treated according to the guidelines. In another study focusing on guideline conformity in breast cancer therapy in Southern Germany, 70.2% of all patients were treated ‘guideline-conforming' [26]. Although the rates of guideline conformity seem to be higher in both groups presented in here, classification algorithms of guideline conformity might vary, resulting in these differences.…”
Section: Discussionmentioning
confidence: 75%
“…One reason for this high concordance between treatment modalities in both departments is the high adherence to current national breast cancer treatment guidelines [19], ranging between 78.0 and 95.6% of all indications being treated according to the guidelines. In another study focusing on guideline conformity in breast cancer therapy in Southern Germany, 70.2% of all patients were treated ‘guideline-conforming' [26]. Although the rates of guideline conformity seem to be higher in both groups presented in here, classification algorithms of guideline conformity might vary, resulting in these differences.…”
Section: Discussionmentioning
confidence: 75%
“…Understanding the reasons for differences between 'real-world' treatment decisions and guideline recommendations will enable further guideline clarification. Furthermore, lack of adherence to the guideline-recommended treatments may negatively affect quality of care in patients with BC 2,[7][8][9] . This chart review is the first that evaluates actual physician-reported treatments from adjuvant therapy to completion of three lines of treatment in the advanced BC setting for the purpose of providing evidence of HT and chemotherapy treatment patterns in Europe and assessing the results against guideline recommendations in order to highlight issues requiring further clarification.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that a higher number of treated patients leads to better survival due to superior organization and training of health care professionals. Others studies report improved survival for patients who are treated according to guidelines as compared to those who are not [6,14,15]. Based on these facts, it could be hypothesized that patients who are treated in certified breast centers (CBC) might have a better prognosis than patients who are not.…”
Section: Introductionmentioning
confidence: 99%